Present Situation of Renewable Energy in Bangladesh: Renewable Energy Resources Existing in Bangladesh (Global Journals of Research in Engineering, 2013)
Bangladesh is a developing country, it has probability to progress towards increasing the demand of energy .Now a day, Bangladesh is facing energy crisis. In Bangladesh, around 70% of people having lack accesses to electricity and most of them are living in the village. Among them about 40% of them are living in below poverty line. On the other hand climate change puts addition threats to development. To combat these situations, renewable energy technology stands out to be one of the prospective sources to meet its unprecedented energy demand and can contribute to achieve sustainable development as a country has a plentiful supply of renewable sources of energy. This paper investigates the prospect, trend, utilization and its technology as well as reviews the policy and institutions and opportunities of renewable energy technology towards sustainable development and climate change mitigation is context of Bangladesh.
Keywords: renewable energy; solar energy; biogas energy; wind energy; hydro-power energy; geo-thermal energy; tidal energy; bangladesh; ocean wave energy; radia